A relationship of reciprocal influence: Singapore company law and the economy - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2018)
A strong reciprocal relationship has existed between Singapore Company Law (“SCL”) and the economy since Independence in 1965. Swift Parliamentary responses to economic events and successful implementation of Government policies has made it possible to clearly attribute cause and effect to statutory amendments and economic events in turn, proving the reciprocal relationship between the two. The first theme of this paper seeks to explain the fundamental characteristics of SCL that have resulted in such an unusually strong reciprocal relationship: the 1) Autochthonous nature of SCL; 2) Responsive nature of legislation; and 3) Government control at multiple levels of implementation. The second theme examines the interplay between 1) Domestic political and economic events; and 2) Foreign laws and economic events in influencing legislative responses over time and their impact on SCL. This will be done through an examination of four key areas of SCL over fifty years of Singapore economic history.